Research status, development trends, and the prospects of cultivated land risk - Zhao, Zhenting; Lei, Ming; Wen, Liangyou; Xie, Enyi; Kong, Xiangbin (Frontiers in Environmental Science, 2023)
Cultivated land risk poses a critical threat to food security, and managing it is crucial for sustainable land use. To effectively manage this risk, it is essential to identify different types of cultivated land risk, understand their development trends, and research hotspots. This review constructs a comprehensive search strategy for subject terms in CiteSpace to analyze 12,581 literature sources related to cultivated land risk. Through tracking hot spots in cultivated land risk research, we have identified two main phases over the past 20 years. The first phase (2002-2015) focused on exploring various types of cultivated land risk, including soil, nitrogen, sewage sludge, organic matter, and carbon sequestration. Three keywords ： soil, nitrogen, and sewage sludge were studied extensively during this period, with research on agricultural intensification, transport conservation, all aimed at enhancing the theoretical framework concerning cultivated land risk. The second phase (2015-2022) emphasized in-depth research into the mechanisms behind the generation of cultivated land risk. Key topics included methods and models for cultivated land risk research, source analysis, and source apportionment, as well as potentially toxic element and random forest analyses. This phase saw a shift towards a more comprehensive understanding of cultivated land risk, with a focus on uncovering underlying causes and developing effective mitigation strategies. Our research has identified three pivotal steps aimed at reducing cultivated land risk: (1) Rigorous Land Use Management: Implement stringent land use regulations to safeguard high-quality land resources. (2) Sustainable Agricultural Practices: Curtail the utilization of chemical fertilizers and pesticides, fostering improved soil fertility and minimizing environmental repercussions. (3) Robust Environmental Oversight: Establish a robust monitoring network to consistently track environmental concerns, concurrently encouraging the adoption of eco-friendly farming techniques. This comprehensive review holds substantial theoretical significance in advancing the agenda of sustainable cultivated land management and effectively alleviating the perils linked with land use alterations.